2011
DOI: 10.1016/j.neuroscience.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Phox2 upregulates expression of norepinephrine transporter and dopamine β-hydroxylase in adult rat brains

Abstract: Degeneration of the noradrenergic locus coeruleus (LC) in aging and neurodegenerative diseases is well documented. Slowing or reversing this effect may have therapeutic implications. Phox2a and Phox2b are homeodomain transcriptional factors that function as determinants of the noradrenergic phenotype during embryogenesis. In the present study, recombinant lentiviral eGFP-Phox2a and -Phox2b (vPhox2a and vPhox2b) were constructed to study the effects of Phox2a/2b over-expression on dopamine β-hydroxylase (DBH) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 64 publications
(83 reference statements)
3
33
1
Order By: Relevance
“…Such divergent expression of Phox2a and Phox2b may indicate differences in their functions, and leads to the notion that expression of Phox2b is not necessary for the maintenance of the noradrenergic phenotype in the adult brainstem (Card et al 2010). However, our previous study (Fan et al 2011) and the current work showed that Phox2b is expressed in the LC of adult Fischer 344 rats. More importantly, gene expression and proteins of Phox2a and Phox2b are found in the LC of humans at ages ranging from 18–77 years (Table 1).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Such divergent expression of Phox2a and Phox2b may indicate differences in their functions, and leads to the notion that expression of Phox2b is not necessary for the maintenance of the noradrenergic phenotype in the adult brainstem (Card et al 2010). However, our previous study (Fan et al 2011) and the current work showed that Phox2b is expressed in the LC of adult Fischer 344 rats. More importantly, gene expression and proteins of Phox2a and Phox2b are found in the LC of humans at ages ranging from 18–77 years (Table 1).…”
Section: Discussioncontrasting
confidence: 68%
“…Protein levels of Phox2a and Phox2b from rat LC and cultured cells were determined by western blotting as reported previously (Fan et al 2011). Briefly, these samples were prepared by homogenization, centrifugation and measurement of protein concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…For the immunofluorescence staining experiments, the immunofluorescence staining method is similar to that described previously (Fan et al, ). Briefly, brain sections were pre‐incubated in 5% bovine serum albumin in phosphate‐buffered saline supplemented with 0.2% Triton‐X 100 for 1 h at room temperature, followed by incubation with the primary polyclonal antibody against DBH raised from rabbit (1:500; Protos Biotech Corp, New York, NY) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Phox2b gene expression persists in various structures in adult rats and human [21,40], and various findings indicate that it plays a role in maintaining the function of noradrenergic neurons in the adult [41]. Recent studies have also shown residual cardiorespiratory responses in prevalently younger CCHS patients, thus suggesting age-dependent mechanisms such as the developmental reconfiguration of respiratory circuits or the continuing loss of vulnerable cell populations within them due to the expression of an altered PHOX2B transcription factor [42].…”
Section: -Kdg Modulates Phox2b Gene Expression Via Progesterone Nucmentioning
confidence: 99%